The Effect of the Target Arrangement and Target Materials Properties on the Penetration Depth (Advances in Military Technology, 2020)
The article is focused on the development of the new calculation method of jet penetration into the target using AUTODYN simulation. The jet formation, its penetration capability dependence on both, the standoff distance and the properties of targets are studied. Parameters used in this study are: optimal standoff at 180 mm, the gaps between the plates are 10 mm and 20 mm and the target composed of Armox 440T and Steel S235JR+N plates.  Marker points are utilized on the liner and the Armox 440T target to find out the effect of the jet on the target. Experiments were carried out to confirm the results of simulation method.
Keywords: ANSYS AUTODYN; Eulerian grid; jet formation; Lagrangian grid; penetration – standoff curve; PG-7V; standoff